1995
DOI: 10.1127/ejm/7/6/1299
|View full text |Cite
|
Sign up to set email alerts
|

Non-ideal solid-solution in garnet: crystal-structure evidence and modelling

Abstract: Crystal-chemical characterization of 281 gamets, representative of most geologic environments, has allowed distortion of the X, Y and Z polyhedra to be examined as a function of chemical composition, allowing us to understand the reasons for compositional preferences in nature. Pyralspites [with E(Mg,Fe,Mn) as the dom inant X cationsl and ugrandites (with Ca as the dominant X-cation) are separated by a significant compositional gap (1.5 to 2.1 Ca apfu). The existence and width of this gap have been explained o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 0 publications
1
24
0
Order By: Relevance
“…They are fundamental not only from the technological point of view but also represent the main constituents of the Earth's lower crust, upper mantle and transition zone (Anderson 1986(Anderson , 1989Ungaretti et al 1995). For these reasons, the accurate evaluation of the thermodynamic properties of such compounds is of great interest.…”
Section: Introductionmentioning
confidence: 99%
“…They are fundamental not only from the technological point of view but also represent the main constituents of the Earth's lower crust, upper mantle and transition zone (Anderson 1986(Anderson , 1989Ungaretti et al 1995). For these reasons, the accurate evaluation of the thermodynamic properties of such compounds is of great interest.…”
Section: Introductionmentioning
confidence: 99%
“…A sketch of the cubic garnet crystal structure (e.g., Gibbs and Smith 1965;Ungaretti et al 1995) is shown in Fig. 2.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the similar radii of 8-coordinated Li + (r = 0.92 Å) and Mg 2+ (r = 0.89 Å) (Shannon 1976), many geometrical parameters of the X site in LiMGt and pyrope are also comparable, e.g., mean X-O bond length, mean O-O edge distance, and dodecahedral volume (Table 3). Nonetheless, the dodecahedron in LiMGt is the most distorted of all silicate garnets, as measured by the bond-length distortion index (Renner and Lehmann 1986) or, more simply, by the difference between the two crystallographically independent X-O4 and X-O2 bond lengths [Δ(X-O)] (Ungaretti et al 1995) (see Fig. 1 for the atom labels).…”
Section: Resultsmentioning
confidence: 99%